The Impact Of Deforestation As An Idea In The Creation Of Painting - Nataprawira, Muhammad Rafli Ramdhani; Mustika, I Ketut; Setem, I Wayan (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2024)
This thesis contains a description of the creation of a work of painting with the theme "The Impact of Deforestation as an Idea in The Creation of Painting" which was inspired by reading a book which reminded the author of his visit to Kalimantan. This will discuss the impact of deforestation in Indonesia. Indonesia is the largest archipelagic country in the world, with its vast territory, Indonesia is known for its very diverse cultural, ethnic and natural riches, and as the Lungs of the World. However, the serious problem currently facing Indonesia is deforestation. Deforestation is the activity of cutting down forests where the land is converted for non-forest use. This change in forest land causes disruption of environmental conditions such as natural disasters, extinction of flora and fauna, global warming and climate change. The aim to be achieved in creating this work is to understand the impact of deforestation in Indonesia through creativity and imagination in the form of paintings using various techniques, media, considering the elements and principles of fine art. From the theme above, there are 6 (six) works that can be realized from the impact of deforestation which can provide an overview of the impact of deforestation in Indonesia.